The Deformational Journey of the Nazca Slab From Seismic Anisotropy. Issue 11 (3rd June 2020) - Agrawal, Shubham; Eakin, Caroline M.; Portner, Daniel E.; Rodriguez, Emily E.; Beck, Susan L.
Abstract: The Andean subduction zone is an excellent place to study deformation within a subducting slab as a function of depth, owing to the varying and well‐resolved geometry of the subducting Nazca slab beneath South America. Here we combine the results of source‐side shear wave splitting with the latest regional tomography model to isolate intraslab raypaths and determine the spatial distribution of anisotropy within the Nazca slab. We observe that in the upper mantle, the intraslab anisotropy appears strongest where the slab is most contorted, suggesting a strong link between anisotropy and subduction‐related slab deformation. We identify a second source of anisotropy ( δ t ∼ 1 s) within the subducting slab at lower mantle depths (660–800 km). The surrounding mantle and transition zone appear largely isotropic, with deep anisotropy concentrated within the slab as it deforms while entering the higher‐viscosity lower mantle. Plain Language Summary: Few observations exist of how a tectonic plate deforms as it descends deep into the Earth's interior at a subduction zone. Carefully selected seismic waves that mostly travel through this subducting plate, or slab, provide some of the most direct measurements of how the slab behaves as it sinks through the upper mantle (0–410 km) and the mantle transition zone (410–660 km). Studying the polarization of seismic waves allows us to detect and infer the pattern of deformation within the Earth's interior. Using this technique, we find that the Nazca slab in the Andean subduction zone in South America has undergone internal deformation during the process of subduction, in particular where the slab's 3‐D shape changes. Furthermore, we find that the deeper Nazca slab (≥660 km) appears to undergo further deformation as it interacts with the stiffer uppermost lower mantle. Key Points: We find a notable presence of anisotropy within the Nazca slab in both the upper and lower mantle Upper mantle slab anisotropy is strongest where the slab geometry is most contorted and deformed Widespread anisotropy is observed at the base of Nazca slab where it penetrates the higher‐viscosity lower mantle